2018
DOI: 10.1096/fj.201701452rr
|View full text |Cite
|
Sign up to set email alerts
|

ZAP70 expression enhances chemokine‐driven chronic lymphocytic leukemia cell migration and arrest by valency regulation of integrins

Abstract: The ζ-associated protein of 70 kDa (ZAP70) is expressed in the aggressive form of B-cell chronic lymphocytic leukemia (CLL). Moreover, the integrin very late antigen (VLA)-1 is highly expressed on subtypes of CLL that are associated with high proliferation rates in the lymph node context. We herein identify a critical role for ZAP70 in chemokine-mediated, inside-out signaling to integrins in trisomy 12 carrying Ohio State University-CLL cell lines derived from a patient with previously treated CLL. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 55 publications
(95 reference statements)
1
30
0
Order By: Relevance
“…This finding is consistent with previous studies showing ZAP-70 expression in CLL cells correlates with CCR7 expression, induced by IgMmediated ERK activation, thus enhancing the migratory ability to CCL19 and CCL21 (34,35). A recent study has further evidenced this in CLL patients, and observed that ZAP-70 positive CLL cells migrated more to CCL19, CCL21, and CXCL12 by controlling the chemokine-driven clustering of the integrins VLA-4 and LFA-1 (36). Moreover, ZAP-70 expression also correlates with CCR7/CXCR4 expression in B cell precursor ALL disease and here promotes migration toward CCL19/CXCL12 in the central nervous system (37).…”
Section: Cell Migrationsupporting
confidence: 92%
“…This finding is consistent with previous studies showing ZAP-70 expression in CLL cells correlates with CCR7 expression, induced by IgMmediated ERK activation, thus enhancing the migratory ability to CCL19 and CCL21 (34,35). A recent study has further evidenced this in CLL patients, and observed that ZAP-70 positive CLL cells migrated more to CCL19, CCL21, and CXCL12 by controlling the chemokine-driven clustering of the integrins VLA-4 and LFA-1 (36). Moreover, ZAP-70 expression also correlates with CCR7/CXCR4 expression in B cell precursor ALL disease and here promotes migration toward CCL19/CXCL12 in the central nervous system (37).…”
Section: Cell Migrationsupporting
confidence: 92%
“…Moreover, CXCR4-induced ZAP70 activation results in phosphorylation of Vav1, a guanine nucleotide exchange factor for Rac/Rho GTPases, and its dissociation from talin enabling talin-integrin association and hence, inside-out signaling and activation of the integrin very late antigen-4 (VLA-4) in T cells (1921). Remarkably, we recently identified ZAP70, which is aberrantly expressed in chronic lymphatic leukemia (CLL), to enhance chemokine-driven CLL arrest by promoting integrin clustering (22).…”
Section: Introductionmentioning
confidence: 99%
“…CCR7 has been reported to influence the lymph node metastasis of cervical cancer, prostate cancer cell migration, and mammary cancer cell stemness (Boyle et al, 2017;Dai et al, 2017;Maolake et al, 2018). Tyrosine kinase ZAP70 has been identified to play a key role in T cell activation and the immune response (Fu et al, 2016;Alsadeq et al, 2017;Laufer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%